Efficacy of the ABCDE health education poster in improving HIV prevention knowledge among coal mine workers - Farlen, Marlika; Yunita, Laurensia; Yuliana, Fitri; Iswandari, Novita Dewi; Widodo, Hariadi (Ananda - Health & Education Foundation, 2026)
Background: Coal mine workers are a highly vulnerable population to HIV transmission due to their unique working conditions, including remote locations and prolonged separation from family, which often lead to high-risk behaviors. Preliminary assessment among workers at PT. X in Barito Utara indicated a significant gap in HIV prevention knowledge. Objective: This study aimed to analyze the efficacy of the ABCDE health education poster in improving HIV prevention knowledge among male coal mine workers. Method: A pre-experimental, one-group pretest-posttest design was utilized. A sample of 30 male workers was recruited using accidental sampling. Data on HIV prevention knowledge were collected via a validated online questionnaire before (pretest) and immediately after (posttest) exposure to the ABCDE poster intervention. The Wilcoxon Signed Rank Test was employed to analyze the difference between pre- and post-intervention scores. Results: The percentages knowledge significantly increased from pretest (72%) to posttest (86%) after the intervention, with the Wilcoxon test yielding a statistically significant result (p <0.001). The highest improvement was observed in younger and more educated workers. Conclusion: The IDI's ABCDE health education poster is an effective, low-cost, and efficient visual tool for rapidly increasing HIV prevention knowledge among coal mine workers. These findings support the integration of targeted visual media into Occupational Health and Safety (OHS) programs to address knowledge gaps in remote industrial settings.